(untitled) - Katarína Žiaková; Dominika Kalánková; Martina Tomagová (University of Ostrava, 2022)
Aim: To provide an overview of instruments measuring nurse professionalism, and to analyze and critically evaluate the psychometric properties of these instruments. Design: A narrative literature review. Methods: A search was made for studies focusing on instruments measuring nurse professionalism using relevant terms. The literature search was conducted between September and December 2020 in two scientific databases: Scopus, and ProQuest. A total of eleven studies featuring instruments to measure nurse professionalism were included in the analysis. A content analysis approach was adopted. Results: We identified eleven self-report instruments measuring nurse professionalism, seven of which were designed to measure nurse professionalism in general, and four which measured more specific concepts, such as nursing values or nurse-nurse collaboration. The instruments demonstrated acceptable psychometric properties. Conclusion: There is a lack of research focusing on nurse professionalism in a European context, and in Slovakia in particular. With increasing demands on nursing care, it is necessary to examine this phenomenon within nursing practice. We, therefore, recommend that research be conducted using instruments to measure nurse professionalism in Europe and in Slovakia.